Ethical contestation in architecture for a creative Singapore. - Busenkell, Michaela (Routledge, 2021)
How does the “good life in the city” manifest itself in the spatial production for the creative city projects of Singapore? In this chapter, the urban-ethical question “how should one live in the city?” in the sense of leading a good and successful life is considered from the viewpoint of architects and policy makers and the question “how should one build for a ‘creative city’ in Singapore?” Following Lefebvre’s concepts of perceived, conceived and lived space, differing understandings of what constitutes a “good” construction of space brings the ethical dispositions of architects, institutions and actors of Singapore’s creative city program into focus. From the perspectives of governance strategies, processes of subjectivation and social creativity, architectural case studies reveal which ethical connotations constitute architecture. The research analyzes the tensions that emerge as architects and buildings aim to satisfy the pragmatic government’s interest in economic performance, global city status and nation-building processes on the one hand, and the notion of imagining and performing a specific, context-based, Singapore idiom on the other. With the case study of the Esplanade –Theatres on the Bay, the first cultural icon of the creative city program, an example is presented of the ways in which the discussion on architecture in Singapore refers to the politics of identity and questions of civil society, participation and freedom.
Keywords: Stadtgesellschaft; Wertvorstellung; Lebensweise; Kreatives Milieu; Stadtentwicklung; Stadtsoziologie; Planungsleitbild; Planungsprogramm; Kultureinrichtung; Architekturästhetik; Transformationsprozess; Fallstudie